Headache onset after vaccination against SARS-CoV-2: a systematic literature review and meta-analysis - Castaldo, Matteo; Waliszewska-Prosół, Marta; Koutsokera, Maria; Robotti, Micaela; Straburzyński, Marcin; Apostolakopoulou, Loukia; Capizzi, Mariarita; Çibuku, Oneda; Ambat, Fidel Dominique Festin; Frattale, Ilaria; Gadzhieva, Zukhra; Gallo, Erica; et al. (The journal of headache and pain, 2022)
BACKGROUND: Vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are used to reduce the risk of developing Coronavirus Disease 2019 (COVID-19). Despite the significant benefits in terms of reduced risk of hospitalization and death, different adverse events may present after vaccination: among them, headache is one of the most common, but nowadays there is no summary presentation of its incidence and no description of its main features. METHODS: We searched PubMed and EMBASE covering the period between January 1st 2020 and August 6th, 2021, looking for record in English and with an abstract and using three main search terms (with specific variations): COVID-19/SARS-CoV-2; Vaccination; headache/adverse events. We selected manuscript including information on subjects developing headache after injection, and such information had to be derived from a structured form (i.e. no free reporting). Pooled estimates and 95% confidence intervals were calculated. Analyses were carried out by vaccine vs. placebo, by first vs. second dose, and by mRNA-based vs. "traditional" vaccines; finally, we addressed the impact of age and gender on post-vaccine headache onset. RESULTS: Out of 9338 records, 84 papers were included in the review, accounting for 1.57 million participants, 94% of whom received BNT162b2 or ChAdOx1. Headache was generally the third most common AE: it was detected in 22% (95% CI 18-27%) of subjects after the first dose of vaccine and in 29% (95% CI 23-35%) after the second, with an extreme heterogeneity. Those receiving placebo reported headache in 10-12% of cases. No differences were detected across different vaccines or by mRNA-based vs. "traditional" ones. None of the studies reported information on headache features. A lower prevalence of headache after the first injection of BNT162b2 among older participants was shown. CONCLUSIONS: Our results show that vaccines are associated to a two-fold risk of developing headache within 7 days from injection, and the lack of difference between vaccine types enable to hypothesize that headache is secondary to systemic immunological reaction than to a vaccine-type specific reaction. Some descriptions report onset within the first 24 h and that in around one-third of the cases, headache has migraine-like features with pulsating quality, phono and photophobia; in 40-60% of the cases aggravation with activity is observed. The majority of patients used some medication to treat headache, the one perceived as the most effective being acetylsalicylic acid.
Keywords: Vaccination; Headache; BNT162b2; bolesti hlavy; vakcinace; BNT162 Vaccine; Adverse Event; ChAdOx1; vakcína BNT162; lidé; Humans; COVID-19; SARS-CoV-2